New genus, species, and faunistic records of the tribe Ripidiini (Coleoptera: Ripiphoridae) from the mainland of China - Jiang, Lan-Xing; Pan, Zhao (Zootaxa, 2024)
Anatoripidius cylindricus gen. & sp. nov., a new genus and species of Ripidiinae Gerstaecker, 1855 from Guangdong, China, is described and illustrated. The new genus is distinguished from other ripidiine genera by the combined characters that include postocular ommatidia missing, mouthparts strongly reduced, 11-segmented antennae, and others dealing with hind wings, and tarsal formula. A key to the extant genera of Ripidiini from the Palaearctic and Oriental regions is presented. Furthermore, Ripidius longicollis (Schilder, 1923) is newly recorded for the mainland of China, as well as redescribed and illustrated.